2005
DOI: 10.4103/0972-9941.16529
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic splenectomy using conventional instruments

Abstract: Introduction:Laparoscopic splenectomy (LS) is an accepted procedure for elective splenectomy. Advancement in technology has extended the possibility of LS in massive splenomegaly [Choy et al., J Laparoendosc Adv Surg Tech A 14(4), 197–200 (2004)], trauma [Ren et al., Surg Endosc 15(3), 324 (2001); Mostafa et al., Surg Laparosc Endosc Percutan Tech 12(4), 283–286 (2002)], and cirrhosis with portal hypertension [Hashizume et al., Hepatogastroenterology 49(45), 847–852 (2002)]. In a developing country, these adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…12 Several operative approaches are in practice to access the splenic vessels prior to mobilization of the spleen to minimize bleeding during surgery. [13][14][15][16][17][18] Ligation of splenic vessels prior to splenic mobilization allowed partial emptying of the spleen, thus diminishing its size, facilitating auto transfusion, and decreasing the risk of hemorrhage as concluded by several authors. [19][20][21][22][23] Asoglu et al reported effective control of intraoperative bleeding with no extension of the operative time and low conversion rate during laparoscopic splenectomy with early ligation of the splenic artery before splenic lysis.…”
Section: Discussionmentioning
confidence: 93%
“…12 Several operative approaches are in practice to access the splenic vessels prior to mobilization of the spleen to minimize bleeding during surgery. [13][14][15][16][17][18] Ligation of splenic vessels prior to splenic mobilization allowed partial emptying of the spleen, thus diminishing its size, facilitating auto transfusion, and decreasing the risk of hemorrhage as concluded by several authors. [19][20][21][22][23] Asoglu et al reported effective control of intraoperative bleeding with no extension of the operative time and low conversion rate during laparoscopic splenectomy with early ligation of the splenic artery before splenic lysis.…”
Section: Discussionmentioning
confidence: 93%
“…the bleeding is either from capsule or from the splenic vessels which are more prone for injury during dissection of splenic vessels which is used in all studies mentioned above except in F.Romano et al study who used only ligasure as we did in our study. In our study we use small Pfannenstiel incision to retrieve spleen from abdominal cavity, that was the same way used by Ahmed nada et al (20) and A.N.Dalvi et al (24) . in 3 of our patients we used retrieval bag to retrieve the spleen from site of 10mm port this method used by F.Romano et al (23) patients and in his study he explain that the cause of conversion due to position because most of conversions occur in patients who operated in supine position .…”
Section: Resultsmentioning
confidence: 99%
“…This technique is used even in the case of splenomegaly operated laparoscopically with blood vessels with diameters above 7 mm, because after the ligation of the splenic artery, the blood flow is much reduced, especially if the short vessels of the gastrosplenic ligament are cut shortly afterwards. For the hilum vessels section there is the alternative to use vascular staplers [16,17], conventional ligatures [18] or hemoclips [19]. We preferred vascular sealing devices that can cut the vessels near the surface of the spleen, without damaging the pancreatic tissue, swollen, infiltrated with blood in this case.…”
Section: Discussionmentioning
confidence: 99%